PENGARUH KETERSEDIAAN PENTAGONAL ASSET TERHADAP KEBERLANGSUNGAN HOME INDUSTRI KACANG RENDANG DALAM KERANGKA EKONOMI ISLAM (Studi Kasus: Home Industri Nagari Sundata Selatan, Kecamatan Lubuk Sikaping, Kabupaten Pasaman) - Anisa Talim; Yenty Astarie Dewi (CV. Adiba Aisha Amira, 2025)
This research is motivated by the producers of rendang peanut industry who run their business fromgeneration to generation in South Sundata Village, Lubuk Sikaping District, Pasaman Regency, still experiencing an increase and decrease in income in the production process. The purpose of this study was to determine the effect of the availability of Pentagonal assets on the sustainability of the Rendang Peanut Home Industry in South Sundata Village, Lubuk Sikaping District, Pasaman Regency. The research method used is quantitative research with a descriptive approach. This research is a field research using a questionnaire (Likertscale) with a research sample of 9 respondents. Data analysis techniques using Validity Test, Reliability Test, Normality Test, Simple Linear Regression Test, T Test, and Determinant Coefficient Test. Based on the results of the study, the author found the results of the T Test that the Pentagonal Asset (X) experience variable consisting of Human capital (X1) has a sigvalue of 0.031 (sig<0.05), Natural capital (X2) has a sigvalue of 0.007 (sig<0.05), Financial capital (X3) has a sigvalue of 0.031 (sig<0.05), Social capital (X4) has a sigvalue of 0.020 (sig<0.05), Physical capital (X5) has a sigvalue of 0.007 (sig<0.05) then it can be said that there is a significant influence between the Pentagonal Asset (X) variable on the Sustainability of Home Industry (Y) in rendang peanut producers in South Sundata Village, Lubuk Sikaping District, Pasaman Regency so that Ho is rejected and H1 is accepted. So it can be concluded that the proposed hypothesis can be accepted because the sigvalue is <0.05.